Estimation of stature from cephalometric measurements among male Muslims of Manipur, India - Devi, Thoudam Bedita; Singh, Soibam Jibonkumar (International Journal of Research in Medical Sciences, 2017)
Background: Stature as is one such important anthropometric parameter which helps in personal identification of an individual. The present study attempts to reconstruct stature from some selected cephalometric measurements among 200 male Muslims of Manipur by using standard measurement techniques. Methods: For the purpose of present study, eight cephalometric dimensions of each subject along with their stature were collected from 200 male Manipuri Muslims, (age between 20 to 60 years) of the four valley districts of Manipur viz. Imphal east, Imphal west, Thoubal and Bishnupur following the methods of Singh and Bhasin and Nath. Results: Data analysis reveals significant co-relation between stature and various cephalometric measurements under study. Total facial height shows the highest correlation co-efficient value (r=0.381) while Upper facial height the least (r=0.112). Multiplication factors are found to vary from other populations of Manipur so far studied thus revealing inter- population variation within the state. Simple regression equations for estimating stature are also formulated for these population. Conclusions: The findings of the estimation of stature using multiplication factor and Linear regression equation on the present population varies from the findings on other populations studied by other researchers. Hence in conclusion, it is confirmed that means of stature estimation i.e. multiplication factors and regression equations are population specific. Therefore, derived formulae for a population should not be used to other populations.